National Healthcare Transformation Program in Saudi Arabia: Awareness of the New Models of Care Among Health Professionals - Althuwaybi MA; Alshammari TM; Tharkar S; Alodhayani AA; Al-Muammar M; Abulmeaty M; Almutari KM (Risk Management and Healthcare Policy)
Mohammed A Althuwaybi,1,2 Thamir M Alshammari,3,4 Shabana Tharkar,2 Abdulaziz A Alodhayani,5 May Al-Muammar,2 Mahmoud Abulmeaty,2 Khalid M Almutari2 1Qassim Health Cluster, Qassim, Saudi Arabia; 2Department of Community Health Science, College of Applied Medical Science, King Saud University, Riyadh, Saudi Arabia; 3Department of Clinical Practice, College of Pharmacy, Jazan University, Jazan, Saudi Arabia; 4Pharmacy Practice Research Unit, College of Pharmacy, Jazan University, Jazan, Saudi Arabia; 5Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid M Almutari, Department of Community Health, College of Applied Medical Sciences King Saud University, Riyadh, Saudi Arabia, Email kalmutairim@ksu.edu.saObjective: This study investigated the level of awareness of the new Models of Care (MoC) implemented under Vision 2030’s National Transformation program among healthcare professionals in the Al-Qassim region of Saudi Arabia.Methods: A cross-sectional approach was employed to collect data from 323 healthcare professionals, including physicians and nurses, through an online survey designed to evaluate their awareness of six distinct models of care and their respective components.Results: A significant majority (63.5%) of healthcare providers demonstrated a high level of overall awareness of the MoC. Factors such as holding a higher university degree (p = 0.007), being a physician (p = 0.018), possessing greater work experience (p = 0.017), and having undergone training (p < 0.000) were found to be significantly correlated with increased awareness of the overall model of care. Participants exhibited a strong awareness of preventive care (91%), urgent care (84%), chronic disease care (84%), and mother and childcare (70%) models, whereas awareness of elective (54.8%) and palliative care (55.4%) was notably lower. Both overall and specific awareness levels of MoC were significantly linked to the training received on the subject.Conclusion: The findings indicate a good understanding of the MoC. However, there is substantial potential for improving awareness through structured training programs. Consequently, healthcare policymakers must prioritize the development of structured training programs through training and reinforcement that address all six MoC components.Keywords: awareness, healthcare transformation, National Transformation Program, model of care, Saudi Arabia, Vision 2030